Therapeutic study of Tephrosia purpurea (linn.) root extract on goat tapeworm with special reference to histopathological parameters - L.D. Ghaywat (Director of Academics and Research, Kerala Veterinary and Animal Sciences University, 2021)
Goat farming forms the backbone of the Indian livestock sector. The prevalence of helminth infection is one of the major problems which affects the milk and meat production of small ruminants. It causes diarrhea, anaemia, oedema, bottle jaw and reduce reproductive performance of animals. Anthelmintic resistance and drug residues in animal products like milk and meat are the results of indiscriminate use of anthelminthics by goat owners for helminth control. Herbal anthelminthics are effective alternatives without any harmful effects. The paper presents the anthelminthic potential of the root extract of Tephrosia purpurea (linn.) plant on common tapeworm of goat, Moniezia. The in vitro study showed that the anticestodal activity of T. purpurea (linn.) at 125mg/ml dilution was comparable to that of albendazole. The histopathological study revealed very prominent shrinkage of scolex and suckers, tegument showed puff formation and was ruptured at the marginal position with irregular folds and crumbling of the segments. Longitudinal section of segment showed more marginal serrations indicating crumbling of the body segment as compared to albendazole, leading to the death of the worm.